Development of bedaquiline nanoemulsions intended for paediatric multidrug-resistant tuberculosis: excipient selection and preformulation studies - Ajayi, Taiwo Oreoluwa; Poka, Madan Sai; Witika, Bwalya Angel (Frontiers in Medical Technology, 2024)
Preformulation investigations into the development of drug formulations, encompassing considerations related to the structure of the drug, excipients, composition, and physical attributes are crucial. This phase is pivotal in ensuring the ultimate success of nanoemulsion development. The objective of this study was to evaluate and define the properties of bedaquiline (BDQ) and the necessary excipients for the formulation of self-emulsifying BDQ-loaded nanoemulsions. To determine the saturation solubility of BDQ in various oils, an in-house validated HPLC method was used. Fourier transform infrared spectroscopy was utilised to identify and evaluate the compatibility between BDQ and the selected excipients. The water titration method was used to construct phase diagrams to identify the type of structure that resulted following emulsification and to characterise the behaviour of mixtures along dilution paths. The solubility studies revealed that BDQ exhibited the highest solubility in olive oil, with a solubility of 3.45 ± 0.041 mg/ml. The design space led to the formation of emulsions categorised as Winsor products. Importantly, the FTIR data indicated the absence of any potential interactions between BDQ and the chosen excipients. The preformulation studies were successful and facilitated the selection of compatible and suitable excipients for the formulation of BDQ-loaded nanoemulsions.